2003
DOI: 10.1002/adma.200305274
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Electronic Contributions in Double‐Heterojunction Organic Thin‐Film Solar Cells

Abstract: evaporation was approximately 12 cm 25 cm. The defect layer was created by the designed placement of a mask on the film during evaporation.The As 2 Se 3 coated PES film was then rolled onto the PES core and the resulting preform,~2 cm in diameter, was covered with Teflon tape and consolidated at 260 C (± 5 C) under vacuum for 20 min. The pressure was decreased quickly below 5 torr within the first 5 min. The preform was then quenched in a ±20 C freezer for about 2 min to prevent crystallization and annealed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(55 citation statements)
references
References 21 publications
2
53
0
Order By: Relevance
“…[93][94][95] Also, recently other materials have been proposed as EBL materials which are both organic and inorganic. [96][97][98] The multiple functions of the EBL layer are still a matter of continuing research. 99,100 Recently, by comparing the device performance and interface energy levels of two different EBL materials, 93 it was confirmed that charge transport in BCP is due to damage induced during deposition of the cathode (shown in the EBL layer of Figure 8), while using an EBL with a low IP allows for hole transport to the C 60 /EBL HJ and to direct recombination with electrons photogenerated in the acceptor layer, and this recombination mechanism was also determined for that of the BCP EBL.…”
Section: Double Heterostructurementioning
confidence: 99%
“…[93][94][95] Also, recently other materials have been proposed as EBL materials which are both organic and inorganic. [96][97][98] The multiple functions of the EBL layer are still a matter of continuing research. 99,100 Recently, by comparing the device performance and interface energy levels of two different EBL materials, 93 it was confirmed that charge transport in BCP is due to damage induced during deposition of the cathode (shown in the EBL layer of Figure 8), while using an EBL with a low IP allows for hole transport to the C 60 /EBL HJ and to direct recombination with electrons photogenerated in the acceptor layer, and this recombination mechanism was also determined for that of the BCP EBL.…”
Section: Double Heterostructurementioning
confidence: 99%
“…Moreover, it should be said that, besides better morphology control, device performance can also be optimised by smart device architecture, e.g., by applying hole blocking layers, [100] optical spacers to enhance light absorption in the layer of the same thickness [101,102] and by using the tandem cell architecture, [103][104][105] where two PV cells are added in S. van Bavel, S. Veenstra, J. Loos Figure 4. Volume representation obtained by electron tomography of P3HT nanorods (bright phase) in a P3HT/PCBM bulk heterojunction demonstrating the presences of a genuine 3D co-continuous network and concentration gradients within the thickness of the photoactive layer of both components.…”
Section: Outlook and Challengesmentioning
confidence: 99%
“…[73][74][75] Generally, TiO 2 should be treated at a high temperature of over 400 8C to obtain crystallinity and to allow its use in either the anatase or the rutile phase. Sintered TiO 2 nanoparticles were reported to have an electron mobility of 10 À6 $10 À7 cm 2 Á Vs…”
Section: Titanium Oxide Interfacial Layer Between the Active Layer Anmentioning
confidence: 99%